Eigenvalue Solver for Fluid and Kinetic Plasma Models in Arbitrary Magnetic Topology (Communications in Computational Physics, 2018)
ArbiTER (Arbitrary Topology Equation Reader) is a new code for solvinglinear eigenvalue problems arising from a broad range of physics and geometry models.The primary application area envisioned is boundary plasma physics in magneticconfinement devices; however, ArbiTER should be applicable to other science and engineeringfields as well. The code permits a variable numbers of dimensions, makingpossible application to both fluid and kinetic models. The use of specialized equationand topology parsers permits a high degree of flexibility in specifying the physics andgeometry.